(untitled) (Herald of Journalism, 2016)
Article is devoted to problems of teaching of the section on editing of business documentation. The author studies features of educational and methodical approaches to illumination of this subject, preparation of various types of documents, and also analyzes problems and perspective possibilities of studying of this aspect in a complex of editorial courses.